2005
DOI: 10.1111/j.1540-8191.2005.200489.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Durability of Surgical Arterialization of Coronary Veins for the Treatment of Ischemic Heart Disease

Abstract: In conclusion, these results indicate that arterialization of the coronary veins is not durable and that it is unlikely that this strategy is a useful technique for the revascularization of the ischemic myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The procedure allows performance of sequential bilateral mammary artery grafting combined with selective arterialization of the coronary venous system; ischemia was reduced in all patients and substantial improvement was seen in cardiac function and quality of life, suggesting a better long-term prognosis and the likelihood of extensive application of the technique [24] . In contrast, earlier human studies suggested a lack of durability of arterialization of coronary vein and expressed doubts that the technique was useful for revascularization of the ischemic myocardium [25] .…”
Section: Discussionmentioning
confidence: 94%
“…The procedure allows performance of sequential bilateral mammary artery grafting combined with selective arterialization of the coronary venous system; ischemia was reduced in all patients and substantial improvement was seen in cardiac function and quality of life, suggesting a better long-term prognosis and the likelihood of extensive application of the technique [24] . In contrast, earlier human studies suggested a lack of durability of arterialization of coronary vein and expressed doubts that the technique was useful for revascularization of the ischemic myocardium [25] .…”
Section: Discussionmentioning
confidence: 94%
“…For severe cases of diffuse RCA lesions, CE often fails to create a suitable anastomosis target for subsequent RCA revascularization ( 8 ). Selective coronary vein bypass grafting (SCVBG) can provide retrograde perfusion of the myocardium from the middle cardiac vein (MCV), effectively improving myocardial perfusion of the ischemic area of the RCA ( 9 , 10 ). However, there are few reports on the clinical efficacy of SCVBG.…”
Section: Introductionmentioning
confidence: 99%